Tubercular cold abscess: uncommon location of a common disease - Jindal, Parth; Hashmat , Ahmer; Srivastava , D. C. (International Journal of Research in Orthopaedics, 2023)
Musculoskeletal tuberculosis is not rare to find, but presence of the disease and such extensive involvement at an unusual site without much of bone involvement is rare. Reporting a case of isolated cold abscess in a 60-year-old male with evening rise of temperature, weight loss and diffuse swelling in his leg involving almost entire anterior aspect of leg. Magnetic resonance imaging (MRI) was advised to investigate further and revealed large focal intra medullary heterogenous collection and large lobulated juxtacortical collection in tibialis anterior muscle. Hematoma/organised abscess, incision and drainage was done and sent for Z-N staining which showed acid-fast bacilli. Anti-tubercular treatment was administered- isoniazid (H), rifampicin (R), ethambutol (E), pyrazinamide (Z). Outcome was favourable and patient become symptomatic better. Drainage of the cold abscess and antitubercular coverage produced good results in this rare presentation of tuberculosis.